TOPOLOGY INDEX OF THE COPRIME GRAPH FOR DIHEDRAL GROUP OF PRIME POWER ORDER - Gayatri, Marena Rahayu; Fadhilah, Rifdah; Lestari, Sahin Two; Pratiwi, Lia Fitta; Abdurahim, Abdurahim; Wardhana, I Gede Adhitya Wisnu (Program Studi Matematika, Universitas Nusa Cendana, 2023)
In the field of molecular chemistry, graph theory is utilized to represent the structure of a molecule, where the set of nodes corresponds to its chemical elements and the set of edges represents the bonds within the chemical molecule. Graph theory, a mathematical discipline, finds application in various domains, one of which is group representation. This research will delve into the topic of the topological indices of the coprime graph of dihedral groups. The methodology employed involves reviewing several references related to dihedral groups, coprime graphs, and topological indices. This study yields results in the form of Harmonic index, Harary index, first Zagreb index, Gutman index, and Wiener index.